Gamma-ray and neutron shielding efficiency of Pb-free gadolinium-based glasses - V. P. Singh (2018)
© Shanghai Institute of Applied Physics, Chinese Academy of Sciences, Chinese Nuclear Society, Science Press and Springer Science+Business Media 2016. The radiation shielding efficiency of material depends upon photon attenuation, exposure buildup factors and neutron removal capacity. A newly developed Pb-free gadolinium-based glasses in compositions (80-x) B2O3-10SiO2-10CaO-xGd2O3(where x = 15, 20, 25, 30 and 35 mol%) had completely been investigated for their shielding efficiency with Geant4 simulation for mass attenuation coefficients and neutron total macroscopic cross section and by calculating exposure buildup factors. The exposure buildup factors for photon energy from 0.015 to 15 MeV had been calculated up to 40 mean free paths using five factors geometric progression method. The mass attenuation coefficients of the Pb-free glasses were simulated for energies from 223 to 2614 keV and compared with the possible available experimental results. The neutron shielding efficiency of these glasses was discussed by calculating neutron total macroscopic cross section for energies from 1 eV to 14.1 MeV. Present investigations are found to be very useful for applications in nuclear engineering.